PENGARUH VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DENGAN FEAR OF MISSING OUT (FOMO) SEBAGAI VARIABEL INTERVENING - Fitri Wasilatul Fadilah; Retna Ngesti Sedyati; Riyanto - Efendi; Prima Ratna Sari (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to examine the effect of viral marketing on purchase decisions for O TWO O products on Shopee, with FOMO serving as an intervening variable. This research employed a quantitative approach with an explanatory research design based on the Stimulus–Organism–Response (S-O-R) Theory. Population study is consumers who had purchased O TWO O products through Shopee, with a sample of 130 female respondents aged 17 years and above selected using purposive sampling. The findings indicate that viral marketing has a positive and significant effect on FOMO, FOMO has a positive and significant effect on purchase decisions, and FOMO significantly mediates the relationship between viral marketing and purchase decisions. This study has several limitations, including its focus on female consumers in Jember Regency, the use of self-reported questionnaire data that may introduce subjective bias, and the examination of only viral marketing and FOMO without considering other factors that may influence purchase decisions. The findings suggest that viral marketing strategies capable of increasing consumers' FOMO can encourage purchase decisions on e-commerce platforms.